Delimitation and description of grape-growing regions of Uruguay based on the multicriteria climatic classification system using bioclimatic indexes adapted to culture conditions - Ferrer, M.; Pedocchi, R.; Michelazzo, M.; González-Neves, G.; Carbonneau, A. (Agrociencia Uruguay, 2007)
The correlations among factors: climate, yield, berry composition and vegetative growth individualize the grapegrowing vocation of a zone. The bioclimatic indexes differ, describe and delimit basic grape-growing zones and explaining the response plant-environment. In order to calculate the indexes: Dryness, Heliotermal and Cool Night, information (1961-1990) of 23 meteorological stations distributed in the whole country, was processed. The Multicriteria Climatic Classification System and multidimensional analysis: Principal Components and Cluster, were applied, and mapped using the “SPRING” software. Six climatic types were identified and characterized, being delimited six grape-growing regions. Major wine-growing surface is influenced by water masses, and implanted according to the classification, in two types of grape-growing climates: a) moderately dry, moderate and temperate nights, b) moderately dry, temperate warm and warm nights, favourable conditions to the ripeness and quality components expression. The majority of the country corresponding to conditions of moderately dry, that would allow favourable conditions of ripeness for early vegetative growth detention. The HI values indicate that there would be no restrictions for implantation of vineyards. The CI locates great part of the territory in night temperatures values favourable to the synthesis of positives secondary metabolites. The Index the Temperature of the hottest month differentiates the territory. The six zones delimitation, through this simple index, follows the tendency of CCM, therefore it might represent the first approach to the grape-growing zoning. The wines of the different regions, presented statistical differences in: alcohol contents, total acidity, pH, dry extract and tartaric acid.